2010
DOI: 10.1590/s1516-14392010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Dual-curing, self-adhesive resin cement: influence of the polymerization modes on the degree of conversion and microhardness

Abstract: RelyXTM Unicem, dual-curing self-adhesive resin cement, was tested in order to evaluate the degree of conversion (DC) and Vickers microhardness (VMH). The specimens were prepared into 4 groups (GR). For GR1, the specimens were irradiated with 500 mW.cm -2 during 20 seconds while for GR3 the same intensity was used but the irradiation time was 40 seconds. The GR2 followed the same polymerization mode of the GR1 but a ceramic disk was applied as a light barrier. For the last group, only the chemical polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…4 A number of studies have reported higher degree of conversion under light-polymerization conditions for resin-based materials. 17,18,22 …”
Section: Effect Of the Setting Reactionmentioning
confidence: 99%
“…4 A number of studies have reported higher degree of conversion under light-polymerization conditions for resin-based materials. 17,18,22 …”
Section: Effect Of the Setting Reactionmentioning
confidence: 99%
“…Many studies reported that light curing could improve the photo-polymerization of dual cure resin cements, while chemical curing was insufficient for polymerization 31,32) . The light curing increased the degree of conversion and the microhardness compared to chemical cured ones 33) . This study reported that light curing significantly improved the µTBS over the chemical curing mode, by which the hypothesis (b) was rejected as well.…”
Section: Discussionmentioning
confidence: 92%
“…Although the used CAD/CAM materials acts as a light barrier during photo initiation of resin luting cements, yet their translucency may play a major role, allowing sufficient delivery of curing wave length to the under lying maturing material. Therefore, a greater degree of conversion leading to harder resin with a more stable color after polymerization (21,22,23,24) .…”
Section: Discussionmentioning
confidence: 99%